2018
DOI: 10.1073/pnas.1803347115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the acid-initiated uncoating of human enterovirus D68

Abstract: Enterovirus D68 (EV-D68) belongs to a group of enteroviruses that contain a single positive-sense RNA genome surrounded by an icosahedral capsid. Like common cold viruses, EV-D68 mainly causes respiratory infections and is acid-labile. The molecular mechanism by which the acid-sensitive EV-D68 virions uncoat and deliver their genome into a host cell is unknown. Using cryoelectron microscopy (cryo-EM), we have determined the structures of the full native virion and an uncoating intermediate [the A (altered) par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 86 publications
4
57
0
Order By: Relevance
“…Hence, VP4 could contribute to the poorly ordered density on the inside of the capsid close to the vertices, attributed primarily to RNA, as well as to the density spanning the capsid. In corroboration of this finding, the presence of a tiny amount of VP4 was recently reported in A-particles of enterovirus D68 induced by acid treatment (49).…”
Section: Fig 1 Legend (Continued)supporting
confidence: 77%
See 2 more Smart Citations
“…Hence, VP4 could contribute to the poorly ordered density on the inside of the capsid close to the vertices, attributed primarily to RNA, as well as to the density spanning the capsid. In corroboration of this finding, the presence of a tiny amount of VP4 was recently reported in A-particles of enterovirus D68 induced by acid treatment (49).…”
Section: Fig 1 Legend (Continued)supporting
confidence: 77%
“…The first modeled residue of the VP1 N terminus (Asn 55) lies in close proximity to the unassigned density near the 2-fold axis inside the particle; therefore, the unassigned density could be the VP1 N termini now traversing the capsid and exposed on the surface of the treated capsid similarly to the interpretation for expanded particles of other enteroviruses (Fig. 6D, red arrows in the inset) (20,26,49). In addition, part of this poorly ordered density seen on the exterior could be attributed to a flexible VP3 loop (residues Thr 175 to Asp 183).…”
Section: Fig 1 Legend (Continued)mentioning
confidence: 73%
See 1 more Smart Citation
“…It is generally accepted that the interfaces between pentamer subunits are major sites of structural rearrangement during capsid uncoating. For example, studies have widely documented the formation of pores at these interfaces [67][68][69][70][71][72][73] or the loss of one or more pentamer subunit(s) [53,58,74,75] upon exposure of the picornavirus capsid to denaturing conditions. To identify the hotspot residues that are critical to the binding specificity and stability of the pentamer interfaces, complexes of two opposing protomers at the two-fold axis and two adjacent protomers at the three-fold axis were analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike mature native virions (160S particles), whose capsids form a closed surface, the expanded 135S particles have holes in the capsid at the icosahedral 2-fold and quasi-3-fold axes. These openings permit the externalization of the membraneinteractive N-terminal extension of capsid protein VP1 [11,14] in poliovirus and in the 135S particles of other enteroviruses [19][20][21][22][23][24][25][26] and presumably VP4, which is myristoylated [27]. In vitro studies with model membranes have shown that these polypeptide chains are responsible for anchoring the virus to the host cell membrane [11,28].…”
Section: Introductionmentioning
confidence: 99%